A new nuclear function of the entamoeba histolytica glycolytic enzyme enolase: the metabolic regulation of cytosine-5 methyltransferase 2 (Dnmt2) activity - Tovy, Ayala; Tov, Rama Siman; Gaentzsch, Ricarda; Helm, Mark; Ankri, Serge (PLoS pathogens, 2010)
Cytosine-5 methyltransferases of the Dnmt2 family function as DNA and tRNA methyltransferases. Insight into the role and biological significance of Dnmt2 is greatly hampered by a lack of knowledge about its protein interactions. In this report, we address the subject of protein interaction by identifying enolase through a yeast two-hybrid screen as a Dnmt2-binding protein. Enolase, which is known to catalyze the conversion of 2-phosphoglycerate (2-PG) to phosphoenolpyruvate (PEP), was shown to have both a cytoplasmatic and a nuclear localization in the parasite Entamoeba histolytica. We discovered that enolase acts as a Dnmt2 inhibitor. This unexpected inhibitory activity was antagonized by 2-PG, which suggests that glucose metabolism controls the non-glycolytic function of enolase. Interestingly, glucose starvation drives enolase to accumulate within the nucleus, which in turn leads to the formation of additional enolase-E.histolytica DNMT2 homolog (Ehmeth) complex, and to a significant reduction of the tRNAAsp methylation in the parasite. The crucial role of enolase as a Dnmt2 inhibitor was also demonstrated in E.histolytica expressing a nuclear localization signal (NLS)-fused-enolase. These results establish enolase as the first Dnmt2 interacting protein, and highlight an unexpected role of a glycolytic enzyme in the modulation of Dnmt2 activity.